'effort' (Energy Efficiency on-site) – A New Method for Planning and Realization of Energy-efficient Neighbourhoods Under the Aspects of Sustainability. (2015) - Roselt, Kersten; Quaas, Ingo; Genske, Dieter; Klawonn, Ulf; Männel, Linda; Reich, Andreas; Ruff, Ariane; Schwarze, Matthias
Abstract: To meet the challenges of climate change requires the commitment towards a climate-friendly energy production as well as an increased effort for climate-friendly energy use. In order to produce a noticeable reduction in greenhouse gases, it is necessary to increase the share of renewable energy and energy efficiency use in all sectors of consumption. The necessary result can only be achieved in the long term by the inclusion of as many households and businesses in our towns, cities and communities. The crucial spatial unit of this energy-efficiency urban redevelopment has become apparent based on present knowledge of the neighbourhood. Within the system relationship between building and city, lies the major energy optimization potential on a neighbourhood scale – in the sense that maximum energy efficiency may be grouped together in the spatial unit.